2003
DOI: 10.1038/sj.gene.6363978
|View full text |Cite
|
Sign up to set email alerts
|

The SDF1-G801A polymorphism is not associated with SDF1 gene expression in Epstein–Barr virus-transformed lymphoblastoid cells

Abstract: The effects of the SDF1-3 0 A on AIDS progression have been attributed to the altered amount of stromal cell-derived factor 1 (SDF-1). However, the contribution of the SDF1-G801A polymorphism to SDF-1 expression is still unclear. In contrast to fresh peripheral blood mononuclear cells (PBMCs), Epstein-Barr virus (EBV)-transformed lymphoblastoid cell lines (LCLs) express the SDF-1 mRNA. Using EBV-transformed LCLs from 42 individuals with different genotypes, we investigated the SDF-1 mRNA levels and methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In agreement with our prior data CXCR4 protein expression was similarly observed in isolated crypts from human colonic tissues (data not shown). Isolated human peripheral blood monocytes assayed as a control did not express CXCL12 (Kimura et al, 2003). Those data, combined with the amplification of villin and CD45 as control transcripts, indicate that CXCL12 and CXCR4 mRNA expression observed in our mucosal preparations solely reflected epithelial expression and was not the result of contaminating immune cells.…”
Section: Resultsmentioning
confidence: 64%
“…In agreement with our prior data CXCR4 protein expression was similarly observed in isolated crypts from human colonic tissues (data not shown). Isolated human peripheral blood monocytes assayed as a control did not express CXCL12 (Kimura et al, 2003). Those data, combined with the amplification of villin and CD45 as control transcripts, indicate that CXCL12 and CXCR4 mRNA expression observed in our mucosal preparations solely reflected epithelial expression and was not the result of contaminating immune cells.…”
Section: Resultsmentioning
confidence: 64%
“…Similarly, Kimura et al 21 did not detect a significant association between the CXCL12 gene polymorphism and gene expression (CXCL12 mRNA levels) in EBV-transformed lymphoblastic cell lines. Their more recent study 22 on EBV-transformed lymphoblastic cell lines with a heterozygous CXCL12 genotype demonstrated that the polymorphisms other than the CXCL12 G801A polymorphism could have a cis-acting effect on the expression of CXCL12 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results regarding patients undergoing autologous transplantation of haematopoietic stem cells concur with those reported by Benboubker et al 15 The association between the CXCL12 gene polymorphism and the serum levels of CXCL12vwas suggested by Winkler et al 11 However, to date, the exact relationship between the CXCL12 genotypes and the corresponding protein production is not clear and the studies examining the association differ in their methodological approaches. [20][21][22][23] As this mutation lies in the 3 0 UTR of the gene, Winkler et al 11 suggested that this mutation may upregulate transcription of the gene, resulting in more abundant CXCL12, which in turn, inhibits T-tropic HIV-1 and delays the onset of the disease. Arya et al 20 tested this hypothesis in vitro: the wild-type and the mutant CXCL12 gene were cloned and the expression was measured in human and insect cells in culture.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of both CXCR4 and CXCL12 expression by the MDA-MB-435s cell line may reflect their clarification not as mammary carcinoma cells but as melanoma cells (Ellison et al, 2002). Thus, the expression profile acquired during mammary epithelial transformation was characteristically similar to highly migratory leukocytes in that CXCR4 expression predominates over little if any CXCL12 expression (Kimura et al, 2003).…”
Section: Loss Of Cxcl12 Expression In Mammary Carcinomamentioning
confidence: 98%